Investigation of simultaneous ultrasonic processing of polymer-nanoparticle solutions for electrospinning of nanocomposite nanofibers. (August 2018) - Hulsey, Stephanie; Absar, Saheem; Choi, Hongseok
Abstract: The electrospinnability of polymer-nanoparticle solutions prepared by simultaneous ultrasonic liquid processing of poly(ethylene oxide) (PEO) polymer and silicon carbide (SiC) nanoparticles was investigated in this study. PEO-SiC nanocomposite nanofibers were produced by electrospinning of PEO-SiC precursor solutions containing different concentrations of PEO (8–12 wt.%) and SiC (1–3%) nanoparticles. Systematic investigations were then performed by analyzing the rheological properties of the solutions and observing the morphological development of nanocomposite nanofibers using scanning electron microscopy (SEM). The investigations showed that a 12 wt% PEO concentration in the solution allowed sufficient polymer chain entanglement for the formation of defect-free and uniform diameter nanofibers regardless of the concentration of SiC nanoparticles. Fourier transform infrared spectroscopy (FTIR) analysis of the neat PEO polymer and PEO-SiC nanocomposite nanofibers showed that the chemical structure of the base polymer is preserved after being subjected to ultrasonic processing and electrospinning. Shifting of peaks and changes in shape of the complex COC absorbance band in the FTIR spectra of PEO-SiC nanofibers indicated that the SiC nanoparticles can be attracted to hydrophilic groups due to their enhanced surface energies caused by ultrasonic processing. These investigations provide strong support regarding the effectiveness of ultrasonic processing for electrospinning of polymer nanocomposite nanofibers with high concentrations of reinforcement nanoparticles. The research performed in this work will serve as a baseline for future work on scaling up the fabrication of novel nanocomposite nanofibers with enhanced mechanical and physical properties.